A Simplified Method for Evaluating Chitin-Binding Activity Applied to YKL-40 (HC-gp39, CHI3L1) and Chitotriosidase - Keita Suzuki; Hidetoshi Suzuki; Ami Tanaka; Miwa Tanaka; Kairi Takase; Hiromu Takei; Tomoki Kanaizumi; Kazuaki Okawa; Peter O. Bauer; Fumitaka Oyama (Molecules)
YKL-40 is structurally similar to chitotriosidase (CHIT1), an active chitinase, but it lacks chitin-degrading activity while retaining chitin-binding capability. Elevated YKL-40 levels are associated with inflammatory diseases and cancers, making it a valuable biomarker. We previously reported that the W69T substitution in YKL-40 significantly reduces its chitin-binding affinity, identifying W69 as a crucial binding site. In this study, we establish a novel chitin-binding affinity evaluation method using a three-step buffer system to assess the binding strength and specificity of chitin-binding proteins and apply it to characterize YKL-40’s binding mechanism. Our findings confirm that YKL-40, through its key residue W69, exhibits highly specific and robust affinity to chitin. Unlike CHIT1, which has both a catalytic domain (CatD) and a chitin-binding domain (CBD) that allow for diverse binding and degradation activities, YKL-40 lacks a CBD and is specialized for specific chitin recognition without degrading it. Comparative analysis with YKL-39, which does not contain a corresponding W69 residue, highlights the unique role of this residue in YKL-40’s chitin-binding activity that is potentially linked to immune and inflammatory responses. Our evaluation method clarifies YKL-40’s binding properties and provides a versatile approach applicable to other chitin-binding proteins.